2018
DOI: 10.1080/20961790.2018.1445937
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical variations of cannabis smoke from a variety of cannabis samples in New Zealand

Abstract: Studies have compared the chemical properties of tobacco smoke to those of cannabis smoke, with the objective of identifying the chemical attributes responsible for the mutagenicity and carcinogenicity of cannabis smoke. Comparative studies have included small sample sizes and produced conflicting results. The aim of this study was to assess the major chemical and physical variations of cannabis smoke across a range of cannabis samples of different potencies and origins, sourced from the illegal market in New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…We observed a greater proportion of individuals without a history of cancer reporting inhalation methods compared to cancer survivors. This is potentially worrisome because of increasing concern of adverse effects on the respiratory system associated with inhalation of cannabis, as well as some studies suggesting that cannabis smoke may contain toxic components similar to tobacco smoke 46–50 . Conversely, our findings suggest that individuals consuming cannabis for medical purposes had higher odds of using oral consumption, as well as more frequent use.…”
Section: Discussionmentioning
confidence: 53%
“…We observed a greater proportion of individuals without a history of cancer reporting inhalation methods compared to cancer survivors. This is potentially worrisome because of increasing concern of adverse effects on the respiratory system associated with inhalation of cannabis, as well as some studies suggesting that cannabis smoke may contain toxic components similar to tobacco smoke 46–50 . Conversely, our findings suggest that individuals consuming cannabis for medical purposes had higher odds of using oral consumption, as well as more frequent use.…”
Section: Discussionmentioning
confidence: 53%
“…Studies have identified terpenoids as the primary variable in Cannabis smoke across plant varieties, presenting a 40-fold range of total terpenoid content. 33 In tobacco cigarettes, differences in filters, which have been used to reduce harmful volatile constituents in mainstream smoke, impact observed carbonyl yields. 34 In addition, fast-burning, bleached, and flavored papers have been observed to contribute to higher levels of aerosol toxicants.…”
Section: Resultsmentioning
confidence: 99%
“…However, their experimental design differed from ours in that they operated under continuous aspiration conditions while we used more realistic aspiration/rest cycle conditions. Hädener et al [48] used a vaping machine but for dabbing butane hash oil, while Sheehan et al [49] used a smoking machine to characterise the chemical and physical composition of cannabis smoke. This underlines the need to standardise experimental conditions for testing portable cannabis vaporisers.…”
Section: Resultsmentioning
confidence: 99%